Synergy of the mechanical, antifouling and permeation properties of a carbon nanotube nanohybrid membrane for efficient oil/water separation. Issue 22 (23rd May 2017) - Liu, Yanan; Su, Yanlei; Cao, Jialin; Guan, Jingyuan; Xu, Linyan; Zhang, Rannan; He, Mingrui; Zhang, Qi; Fan, Lin; Jiang, Zhongyi
Abstract : PEI and TMC modified carbon nanotube nanohybrid membranes exhibited superior mechanical and antifouling properties, and high flux for oil/water separation. Abstract : For water treatment applications, fabricating a high permeation flux membrane with super-strong mechanical strength and excellent long-term antifouling properties remains a great challenge. In this study, robust, antifouling carbon nanotube (CNT) nanohybrid membranes have been fabricated for oil/water separation. Polyethyleneimine (PEI) with abundant amino groups and a hyperbranched structure is utilized to construct a nanocoating on a CNT surface to enhance their hydrophilicity through multiple interactions between PEI and CNTs. Secondly, the vacuum-assisted self-assembly method is utilized to fabricate free-standing membranes by filtration of CNT dispersions. Finally, trimesoyl chloride (TMC) is utilized to post-modify membranes to enhance the mechanical strength and hydrophilicity and change the surface charge through reaction between amino groups and acyl chloride groups as well as hydrolysis of acyl chloride groups into carboxyl groups. The controlled stacking of CNTs renders membranes with a hierarchical nanostructure and a high porosity, leading to high water flux. The physical and chemical crosslinking renders membranes with high mechanical strength, as measured by atomic force microscopy (AFM) and tensile strength tests. The high hydrophilicity and negatively charged surface render membranes with good antifouling properties, as evaluated by filtration experiments of various oil-in-water emulsions. This study may reveal the great prospects of CNT-based membranes with superior comprehensive properties in water treatment relevant applications.